Ghana Leads West Africa in Transit Reform - Wulf, Luc De (World Bank, Washington, DC, 2012)
Cumbersome transit and customs procedures hinder trade and economic development. Ghana has modified several features of its transit system as part of efforts to improve road-based trade in West Africa. Since 2006 the country's transit reforms have cut the time to process and transport goods crossing the country from five to three days, significantly lowering transport costs. Applying lessons from Ghana could catalyze broader transit reforms in West Africa and other developing regions.